Whose time is it anyway?: factors associated with duration in police custody - Kemp, Vicky; Balmer, Nigel J.; Pleasence, Pascoe (Sweet and Maxwell, 2012)
This study is based on a statistical analysis of police custody records. We earlier examined the take-up of legal advice and now turn our attention to the time people spend in police custody. We find that the average time people are detained seems to have risen over recent years and that a number of factors can impact on the length of detention, including differences found between police stations. The expectations that PACE would restrict the length of time individuals are held in custody were not borne out by the data from the police stations included in this study